ปัจจัยที่มีผลต่อความผูกพันต่อองค์การของบุคลากรโรงพยาบาลในจังหวัดเพชรบูรณ์ - จันทร์เมือง, วิไลวรรณ; ชัยกิจอุราใจ, ประพันธ์ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 3 (2562): Academic Services Journal, Prince of Songkla University, 2019)
การวิจัยเรื่อง “ปัจจัยที่ส่งผลต่อความผูกพันต่อองค์การของบุคลากรโรงพยาบาลในจังหวัดเพชรบูรณ์” มีวัตถุประสงค์ คือ 1) เพื่อศึกษาถึงปัจจัยส่วนบุคคลที่มีผลต่อความผูกพันต่อองค์การของบุคลากรโรงพยาบาลในจังหวัดเพชรบูรณ์ 2) เพื่อศึกษาถึงคุณภาพชีวิตในการทำงานที่มีผลต่อความผูกพันต่อองค์การของบุคลากรโรงพยาบาลในจังหวัดเพชรบูรณ์ 3) เพื่อศึกษาปัจจัยด้านวัฒนธรรมองค์การที่มีผลต่อความผูกพันต่อองค์การของบุคลากรโรงพยาบาลในจังหวัดเพชรบูรณ์ การวิจัยในครั้งนี้เป็นการวิจัยเชิงสำรวจโดยใช้แบบสอบถามเป็นเครื่องมือในการเก็บรวบรวมข้อมูล ประชากรที่ใช้ในการศึกษา ได้แก่ บุคลากรของโรงพยาบาลในจังหวัดเพชรบูรณ์ 10 แห่ง มีจำนวนทั้งสิ้น 2,831 คน คำนวณหาขนาดของกลุ่มตัวอย่างโดยใช้สูตรของ Taro Yamane ที่ระดับความเชื่อมั่นร้อยละ 95 ได้ขนาดกลุ่มตัวอย่าง จำนวน 350 คน เก็บข้อมูลโดยแจกแบบสอบถามให้กับกลุ่มตัวอย่างทั้งหมด 350 ฉบับ ซึ่งได้รับกลับคืนและนำมาวิเคราะห์ได้จริง จำนวน 293 ฉบับ โดยนำข้อมูลมาวิเคราะห์ทางสถิติ ได้แก่ การแจกแจงความถี่ ค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน การทดสอบสมมติฐานโดยใช้ค่า T-test ค่า F-test และการวิเคราะห์ถดถอยแบบพหุคูณ (multiple regression) ผลการวิจัยพบว่า 1) ปัจจัยส่วนบุคคลซึ่งจำแนกตามเพศ อายุ สถานะ ระดับการศึกษา อายุงาน และด้านเงินเดือนที่ได้รับที่แตกต่างกัน พบว่า ทุกด้านยกเว้นด้านเพศส่งผลต่อความผูกพันต่อองค์การอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 2) ปัจจัยคุณภาพชีวิตในการทำงานที่มีอิทธิพลต่อความผูกพันต่อองค์การ พบว่า ประกอบด้วย 3 ด้านที่มีอิทธิพลทางบวกต่อความผูกพันต่อองค์การอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 คือ ด้านการพัฒนาความสามารถของบุคคล ด้านธรรมนูญในองค์การ และด้านความเกี่ยวข้องสัมพันธ์กับสังคม และ 3) ปัจจัยวัฒนธรรมองค์การที่มีอิทธิพลทางบวกต่อความความผูกพันต่อองค์การอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 พบว่า ประกอบด้วย 2 ด้าน คือ ด้านการกำหนดทิศทางและเป้าหมาย และด้านลักษณะที่เป็นเอกลักษณ์ขององค์การ จากการวิจัยพบข้อสังเกตว่าหลายปัจจัยที่มีผลต่อความผูกพันต่อองค์การ อาจส่งผลต่อเนื่องถึงประสิทธิภาพการทำงานของบุคลากรได้ ดังนั้นการศึกษาวิจัยในอนาคตจึงควรศึกษาเพิ่มเติมโดยเน้นถึงความเชื่อมโยงระหว่างปัจจัยด้านความผูกพันต่อองค์การและประสิทธิภาพในการทำงานของบุคลากร เพื่อให้ได้ข้อมูลที่ครอบคลุมมากยิ่งขึ้น คำสำคัญ: คุณภาพชีวิตในการทำงาน, วัฒนธรรมองค์การ, ความผูกพันต่อองค์การ, โรงพยาบาล, จังหวัดเพชรบูรณ์   The research on the topic of “Factors Affecting the Organizational Commitment of the Hospital Employees in Phetchabun Province” was conducted with the following objectives; 1) to study the personal factors influencing the organizational commitment between the hospital employees and its organization in Phetchabun province, 2) to study the quality of work life that affects the organizational commitment with the organization of the hospital employees in Phetchabun province, and 3) to study the organization culture factors that affect the organizational commitment with the organization of the hospital employees in Phetchabun province. The research activities were conducted through a survey method by using a questionnaire as a tool for data collection. The population used in this research was the employees from 10 hospitals in Phetchabun province with a total number of 2,831 persons. The sampling size was calculated by using the Taro Yamane formula at the confidence level of 95 percent and the sample size of 350 persons was obtained. The questionnaires were distributed to all those 350 samples and 293 of them were received in return for further analysis. The data was subjected to a statistical analysis which consisted frequencies, percentage, mean, and standard deviation. The hypothesis testing was conducted using a T-test, an F-test and a multiple regression. The results showed that 1) according to the personal factors as classified by sex, age, status, educational level, work experience, and different salary obtained, it was found that all these factors, except sex, had an impact on the organizational commitment to the organization at the significance level of 0.05., 2) according to quality of work life factors that affect the organizational commitment with the organization of the hospital employees, it was found that there were 3 issues that had a positive impact on the organizational commitment to the organization at the significance level of 0.05, i.e. a development of human capacities, an constitutionalism, and a social relevance, and 3) according to the organizational culture factors that had a positive effect on the organizational commitment with the organization of the hospital employees at the significance level of 0.05, it was found that there were 2 issues, i.e. a determination of directions and goals, and the identity of the organization. From this study, it was observed that some of those factors affecting the overall organizational commitment might have a consequent effect on the performance efficiency of hospital employees. It is, therefore, worth conducting further research in the future by emphasizing on the relationship between the organizational commitment factors and the performance efficiency of hospital employees in order to obtain more comprehensive information. Keywords: quality of work life, organizational culture, organizational commitment, hospital, Phetchabun province